Intravascular Coagulation with Generalized Shwartzman Reaction Induced by a Heparin-Like Anticoagulant (Liquoid) - Evensen, S. A; Jeremic, M; Hjort, P. F (Thrombosis and Haemostasis, 1967)
Liquoid (sodium polyanethol sulfonate), a synthetic heparin-like anticoagulant, produces renal cortical necrosis in rabbits. This lesion is indistinguishable from the generalized Shwartzman reaction which is caused by intravascular coagulation in a prepared animal. We have investigated this apparently paradoxic effect of Liquoid. Our main findings are:1. Liquoid is a potent heparin-like anticoagulant. One mg of Liquoid is neutralized by 1 mg of Polybrene. After intravenous injection the anticoagulant effect is immediate and persists for several hours.2. In larger concentrations, Liquoid precipitates fibrinogen. The precipitation does not depend on an intact coagulation system; the precipitates are dissolved in 30% urea.3. An intravenous injection of 20 mg Liquoid/1500 g body-weight produces an early thrombocytopenia, a progressive depletion of fibrinogen and factor V, the appearance of cold-precipitating material in plasma, and severe renal cortical necrosis.4. Pretreatment with warfarin completely prevents all of these effects, except a moderate fall in platelets.We conclude that Liquoid produces these effects, not by precipitation of fibrinogen, but by intravascular coagulation, probably released through aggregation and damage of the platelets. Thus, intravascular coagulation is again confirmed as the final event in the generalized Shwartzman reaction.